PEMBERDAYAAN KEMITRAAN MELALUI PENGEMBANGAN E-COMMERCE UNTUK UMKM PRODUKSI BONEKA YAN’S COLLECTIONS KARAWANG - Juardi, Didi; Yusup, Eka; Himawan, Irfan Sophan (Universitas Negeri Surabaya, 2025)
Empowering Partnerships Through E-Commerce Development for MSMEs. Yan's Collections Karawang Doll Production includes efforts to increase the competitiveness and sustainability of micro, small and medium enterprises (MSMEs) in the doll production industry. Through the use of e-commerce platforms, it is hoped that MSMEs can reach a wider market, increase sales and strengthen brand awareness. This program includes training for MSMEs, providing access to digital technology, and facilitating collaborative networks between MSMEs and other business actors. In this way, it is hoped that positive synergy can be created to increase skills, innovation and competitiveness of local products in the digital market. This is also expected to contribute to improving the local economy and empowering the surrounding community.